Benefícios compartilhados: um mecanismo para induzir a participação da sociedade no controle dos gastos públicos no Brasil (Economia Aplicada, 2004)
The present paper analyses the incentives individual members of society face to contribute to a nation's corruption control effort. A decision-theoretic model shows that agents do have an interest to dedicate part of their resources to the nation's control effort. However, the opportunity cost ofone individual's dedication and a free rider problem tend to reduce spontaneous provision of support to the corruption control effort. In order to cope with those incentives, a Principal-Agent approach leads to a new mechanism based on directly sharing with the agent the result of his control effort. By means of that mechanism both the opportunity cost and the free rider problem are solved in a way that aligns individual incentives with those of society. Furthermore, this can be made at no extra cost to the government, and indeed, with a positive expected gain to individuals end the government.